2017
DOI: 10.1186/s13584-017-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

The changing roles of community nurses: the case of health plan nurses in Israel

Abstract: BackgroundIn Israel, approximately one-third of the country’s nurses work in community settings – primarily as salaried employees in Israel’s four non-profit health plans. Many health system leaders believe that the roles of health plan nurses have changed significantly in recent years due to a mix of universal developments (such as population aging and academization of the profession) and Israel-specific changes (such as the introduction of extensive quality monitoring in primary care).ObjectivesThe main obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…This aligns with the complex care needs of the patients these nurses have been reported to manage in the UK (Queens Nurse Institute ). Our findings also align with the international research that has explored community and public health nursing roles in countries including Australia (Kelehera & Parker, ; Kemp et al., ; Rodden et al, 2016), Finland (Maijala et al., ), the US (Schaffer, Anderson, & Rising, ) and Israel (Nissanholtz‐Gannot et al., ), the findings of which report the increasing involvement of these nurses in acute episodic care and health promotion activities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This aligns with the complex care needs of the patients these nurses have been reported to manage in the UK (Queens Nurse Institute ). Our findings also align with the international research that has explored community and public health nursing roles in countries including Australia (Kelehera & Parker, ; Kemp et al., ; Rodden et al, 2016), Finland (Maijala et al., ), the US (Schaffer, Anderson, & Rising, ) and Israel (Nissanholtz‐Gannot et al., ), the findings of which report the increasing involvement of these nurses in acute episodic care and health promotion activities.…”
Section: Discussionsupporting
confidence: 87%
“…Community and public health nurses have the potential to make significant contributions to the healthcare needs of various population groups in a variety of community settings and changing population profiles have led to international interest in the work of these nurses (WHO ). Evidence available (Nissanholtz‐Gannot, Rosen, & Hirschfeld, ; Roden, Jarvis, Campbell‐Crofts, & Whitehead , Maijala, Tossavainen, & Turunen, ; Kelehera & Parker, ; Kemp, Harris, & Comino, ), has identified a shift in focus of the care provided by these nurses. In Australia, for example, researchers have reported community nurses to be increasingly working in roles that have moved away from longer term support and care to provision of a more “acutely” focussed episodic care (Kemp et al., ) with increasing involvement in health promotion activities (Kelehera & Parker, ; Roden, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Israeli national survey has shown that Sick Fund community nurses’ current main areas of activity were chronic care, health promotion, quality monitoring, and improvement and home care (Nissanholtz‐Gannot, Rosen, & Hirschfeld, ). While community and public health nurses are not identical roles in Israel, it seems that consideration must be given to matching skills with the health needs of the population in a more integrated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Public health nurses, for example, play a central role in the provision of immunizations and other preventive services to infants and children receiving care in Israel's Maternal and Child Health Clinics [18]. The opportunity for APRNs, PAs and registered nurses to practice to the full extent of their professional capability and capacity can enhance their job satisfaction and improve patient outcomes [19,20]. Clinical pharmacists can also play a critical role in the provision of preventive services and the achievement of desired patient outcomes [21,22].…”
Section: Interprofessional Team-based Care and The Delivery Of Prevenmentioning
confidence: 99%